PENYULUHAN PEMBUATAN PERMEN MODISCO DAUN KELOR (Moringa oleifera) SEBAGAI PENCEGAHAN STUNTING BALITA DI PAMEKASAN - maasyitoh sari latifah; Maya Septriana; Myrna Adianti; Dessy Harisanty; Edith Frederika Puruhito; Rini Hamsidi; Dwi Setiani Sumardiko; Ario Imandiri (Jurnal SADEWA, 2024)
Stunting is the cause of one million child deaths every year, meanwhile Pamekasan Regency is one of the districts on Madura Island with 24 Locations Stunting, five of which are in the Tlanakan Health Center area. A local food ingredient that has the potential to become food for toodlers is Moringa oleifera leaves. Moringa leaves have a high nutritional content, including 22.7% protein, 4.65% fat, 7.92% carbohydrates and 350-50 mg calcium. The purpose of community service is to educate the comunity about stunting prevention, usage of local food and manufacture of moringa modico candy to help prevent stunting in toddlers. The method used was lectures to 75 participants and training in making Modisco candy. An evaluation will then be carried out 1 month later after the implementation of the training to see changes in the toddler's weight to provide conclusions. The results and conclusions obtained are 1) community knowledge has increased about stunting prevention, the use of local food and the manufacture of moringa candy to help prevent stunting in toddlers. 2) There was an increase in the weight of toddlers after 1 month of giving Moringa candy.